Luteal supplementation in in vitro fertilization: more questions than answers - Hubayter, Ziad R.; Muasher, Suheil J. (Fertility and sterility, 2008)
To update clinicians on different regimens of luteal phase supplementation in IVF-stimulated cycles and to identify areas that need further research in this subject. Literature review and critical analysis of published studies on luteal phase supplementation during the last 20 years. Luteal phase supplementation in IVF-stimulated cycles, both in gonadotropin releasing hormone agonist and antagonist protocols, is considered an essential requirement for optimal success rates. The date of initiation and discontinuation of supplemented hormones is not adequately studied in the literature. In most major controlled and randomized studies, there are no significant differences in success rates with progesterone supplementation alone, progesterone and estradiol, progesterone and human chorionic gonadotropin, and human chorionic gonadotropin alone. Success rates seem similar with intramuscular and vaginal progesterone administration with patient preference for the vaginal route. The optimal dose of progesterone has not been studied in a scientific way in the literature. The use of gonadotropin releasing hormone agonists for luteal phase supplementation in antagonist cycles appears to be promising, and is worthy of further investigation.